LATAR BELAKANG SOSIAL BUDAYA DAN PENCAPAIAN PEKERJAAN - PENDAPATAN - Makmuri Sukarno (Jurnal Kependudukan Indonesia, 2006)
This study aims to answer the question 'who will win the competition of getting better jobs and income'. Utilizing regression methods, this study examine the determinants of occupational and income attainment. The results show that children with high educational qualification, whose fathers have high educational and occupational statuses tend to achieve high occupational and income attainment. Children's education was the most powerful predictor of occupational and income attainment. Nevertheless, children's education is strongly determined by parents' education and occupation. This means that inequality in cultural and socio-economic capitals (education and occupation) of parents was not only passed on to their children's education-especially on son-but also to their children's occupation and income. Non-parental backgrounds, such as residence, religion, marital and migration statuses and age have only weak influences on children's occupational and income attainment.